2014
DOI: 10.5348/ijcri-2014100-cr-10411
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic right hemicolectomy after coronary artery bypass grafting using the right gastroepiploic artery: A case report

Abstract: International Journal of Case Reports and Images (IJCRI) is an international, peer reviewed, monthly, open access, online journal, publishing high-quality, articles in all areas of basic medical sciences and clinical specialties.Aim of IJCRI is to encourage the publication of new information by providing a platform for reporting of unique, unusual and rare cases which enhance understanding of disease process, its diagnosis, management and clinico-pathologic correlations. The right gastroepiploic artery (RGEA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Sakamoto et al reported that in laparoscopic cholecystectomy, during dissection of Calot's triangle, it is necessary to ensure that the pedicle is not stretched, and it is important to use a lower pneumoperitoneal pressure (such as 5 mmHg). In laparoscopic colectomy, it has also been reported that care should be taken to avoid the possibility of unexpected excessive stress on the RGEA graft due to positional changes [8,9]. Although gastrectomy is most frequently reported, the RGEA graft may be resected, and a replacement graft may be used from the viewpoint of the lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Sakamoto et al reported that in laparoscopic cholecystectomy, during dissection of Calot's triangle, it is necessary to ensure that the pedicle is not stretched, and it is important to use a lower pneumoperitoneal pressure (such as 5 mmHg). In laparoscopic colectomy, it has also been reported that care should be taken to avoid the possibility of unexpected excessive stress on the RGEA graft due to positional changes [8,9]. Although gastrectomy is most frequently reported, the RGEA graft may be resected, and a replacement graft may be used from the viewpoint of the lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%